Implementation of Mainly Used Edge Detection Algorithms on FPGA - İçer, Yaser; Türk, Mustafa (PLUSBASE AKADEMİ ORGANİZASYON VE DANIŞMANLIK, 2016)
Edge detection has important applications area in image processing field. Today, it is a fact that the image processing used in many fields. Therefore, the applicability of edge detection process in the field is also has great importance. In this study, mainly used edge detection algorithms in the literature; İe. Sobel, Prewitt and Canny algorithms is provided using the verification and inspection on FPGA (Field Programmable Gate Arrays). Program files required for FPGA is prepared by Xilinx System Generator DSP blocks, which can work integrated with Matlab/Simulink. For this study; gray format images, which is stored on the computer has been sent to FPGA with USB configuration port interface on FPGA. Edge detection process is realized by moving subject images from the computer with the same connection to FPGA and then, Sobel, Prewitt and Canny algorihms are applied to the images on FPGA respectively. Edge detection process for the same images are performed by Simulink and FPGA bord at the same time and then, edge detected images obtained from these two environment are compared and also it has been observed on the FPGA resource usage.
Keywords: Engineering; Mühendislik